2020
DOI: 10.1097/jnc.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Are Male Partners the Missing Link to Eliminating Mother-To-Child Transmission of HIV in Sub-Saharan Africa? Evidence From a Retrospective Case-Control Study

Abstract: When male partners of pregnant women living with HIV do not participate in antenatal care, it decreases the uptake of prevention of mother-to-child transmission interventions, which increases the risk of HIV transmission to newborns. We evaluated the association of male partner involvement and vertical HIV transmission at 6 weeks along 4 constructs: antenatal clinic accompaniment, mother's awareness of partner HIV status, disclosure of mother's HIV status to partner, and couple testing. Thirty-three HIV-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This left the woman alone in her journey, having to cope with the stress of being diagnosed and the awareness of HIV transmission risk to her infant. Lack of or minimal spousal/partner involvement is reported as a contributing factor toward increased risk of HIV for HIV-exposed newborns (Mabunda et al, 2021; Nyandat & Van Rensburg, 2020). Some participants had not yet disclosed their HIV status to their partners and families because of the fear of stigmatization and lack of acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This left the woman alone in her journey, having to cope with the stress of being diagnosed and the awareness of HIV transmission risk to her infant. Lack of or minimal spousal/partner involvement is reported as a contributing factor toward increased risk of HIV for HIV-exposed newborns (Mabunda et al, 2021; Nyandat & Van Rensburg, 2020). Some participants had not yet disclosed their HIV status to their partners and families because of the fear of stigmatization and lack of acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…HIV remains a threat to newborns in sub-Saharan Africa despite numerous services available to achieve the goal of an HIV-free generation (Yah & Tambo, 2019). Contributing factors include lack of awareness of HIV status in women of reproductive age, not being on HIV treatment during pregnancy, lack of access to health care services, poverty, and high adolescent pregnancy rates (UNAIDS, 2021) and poor spousal/ partner involvement (Mabunda et al, 2021;Nyandat & Van Rensburg, 2020). Routine "opt-out" testing for all pregnant women, a global strategy to improve case discovery and reduce the risk of transmission once ART is commenced (Kate et al, 2019), has had mixed prenatal care uptake in sub-Saharan Africa (Awopegba et al, 2020).…”
mentioning
confidence: 99%
“…[10][11][12] A case-control study found that mothers living with HIV who had uninfected infants were 14 times more likely to have disclosed their status to their male partners than mothers with HIV-infected infants. 13 Similarly, a national survey in Kenya found that non-disclosure during pregnancy was associated with 12.8 times higher odds of MTCT of HIV. 14 The 2019 Uganda Population-Based HIV Impact Assessment (UPHIA) identified the improvement of disclosure as a critical unmet need in the strive to achieve its 90-90-90 targets.…”
Section: Background and Significancementioning
confidence: 97%
“…In sub-Saharan Africa, interventions to increase partner engagement in antenatal care lead to increased maternal HIV testing, antiretroviral therapy adherence, retention in care, hospital delivery, and decreased parent-to-child HIV transmission [ 1–4 ]. While partner engagement interventions are often successful [ 3–7 ], concerns about engaging difficult partners persist. ‘Difficult’ partners include those who pressure their partner to refuse HIV testing or treatment, stigmatise, threaten to disclose their HIV status, and/or perpetuate intimate partner violence [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%